“Izwe lethu”: l’istanza d’esproprio senza indennizzo della terra, tra aspettative di giustizia sociale e contenimento sindemico Focus su Cape Town (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2020)
After the South African National Assembly approval of the motion by the Economic Freedom Fighters to allow the State to expropriate land without awarding compensation (LEWC), the access of landless black people to a new redistribution seemed on the verge of being resolved once and forever. Even the public auditions to approve the amendment of the property clause in section 25 of the Constitution, seen as an obstacle to expropriation procedures, have been completed. But high expectations are now going to be dramatically deluded. Especially those of shack dwellers, who in informal settlements in the urban outskirts, struggle against the perpetuation of apartheid, and claim the right to move into estates closer to the city centers and the economic opportunities they offer. Due to the spread of Covid-19, evictions to de-densify the informal settlements and transfers of thousands of families in new “ghettos” are under way. Hence, heavy investments to build new quarters in the suburbs are diverting funds from improving LEWC and are likely to fuel a further institutional crisis, within the syndemic one South Africa will be suffering in months to come. The essay starts and concludes with a perspective from the suburbs of Cape Town.
Keywords: Sudafrica; giustizia sociale; riforma fondiaria; riforma costituzionale; COVID-19